Experience Engagement and Connection: Role of Social Media Interactivity among Moroccan Customers of luxury goods - Malika AIT NASSER; Fatima BENSAID (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: The present study aims to determine that perceived social media interactivity significant impact on self-brand connection and intention to purchase. Brand experience play as mediating role and customer brand engagement as moderating among Toyota and Honda vehicles Moroccan customers. Methodology: The cross-sectional approach used for data collection from customers of Moroccan Toyota and Honda vehicles. Total 400 participants, through email filled up online survey to help in data collection. The study analysed by Smart Partial Square (Smart-PLS) statistical software 3.0. Findings: The results of study has significant relationship between social media interactivity, mediating role of customer experience, and moderating role of customer brand engagement with self-brand connection and intention to purchase. Implications/Novel Contribution: This study emphasizes how crucial it is to take cultural differences into account when developing successful marketing plans for luxury car brands. It also adds insightful information to the worldwide conversation on premium branding and customer behavior. The study contributes only customers, managers, marketers that used services of Toyota and Honda vehicle, how customers interact and stimulate to intent in luxury car purchasing.